Bay' Al-Inah dalam Pemikiran Imam Syafi’i dan Imam Malik: Sebuah Kajian Perbandingan - Muchtar Wahyudi Pamungkas; Miftahul Huda (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
This research is motivated by the fact that many people still do not understand the concept of buying and selling, primarily buying and selling bay' al inah. Therefore, the purpose of this study is to provide an understanding to the public about the concept of buying and selling bay' al inah, starting from the transaction procedures to the legal basis of this sale and purchase according to Imam Syafi'i in al-Umm and Imam Malik in al-Muwatta'. This writing uses descriptive qualitative research. To obtain data using a library approach (library research). Data collection techniques are carried out by collecting and reviewing research literature and other data sources relevant to the discussion. The data analysis used is a descriptive qualitative technique, describing and explaining the data of the object of research and comparative analysis, namely looking for points of similarities, differences and the specificity of the thoughts of 2 figures. From this research, it can be concluded that Imam Syafi'i in al-Umm allows this buying and selling because the pillars and conditions are fulfilled, namely, there are buyers, sellers, goods being traded and contracted or consented to. Meanwhile, according to Imam Malik in al-Muwatta', this sale and purchase are declared invalid because there will be an element of Sadd al-Dhari'ah, namely that there will be a lousy purpose from the sale and purchase. This goal leads to prohibited acts, namely usury. Riba here occurs because the prices are different from the two buying and selling.